Pemikiran Pendidikan Ibnu Taimiyah Menurut Majid Irsan Al-Kilani serta Relevansinya bagi Politik dan Kebijakan Pendidikan Islam Masa Kini - Anton Ismunanto (SITASI: Journal of Islamic Studies and Inclusive Education, 2026)
One of the greatest thinkers in Islamic history is Ibn Taimiya. He lived in the middle age era when the Islamic world was facing the long duree war: the Crusade and the battle against the Mongol. In the modern era, he inspired many, especially groups of Islam. Some of these groups are the Muslim Modernist, the Salafi, the Wahabi and the Haraki. Each group tries to implement some aspects of Ibn Taimiya's thought especially which is related to education. This paper tries to examine Ibn Taimiya's Thoughts on education, particularly that which is captured by one of the contemporary Arab educational thinkers and historians, Majid Irsan al-Kilani. This is because Ibn Taimiya didn't specifically write on education and at the same time, he had a large spectrum of thoughts and it is not easy to understand his thought comprehensively by reading his writings directly. So, with the help of al-Kilani's work we will be able to understand Ibn Taimiya's educational thought, relatively completely. After capturing the ideas we will relate his educational thoughts to the real situation of Muslim education, especially in Indonesia. There are many aspects of his ideas that have relevance and benefits for Indonesian Muslims' education, so they can be proposed to policymakers and politicians. This is a library research which processes qualitative data. The technique used is content analysis of al-Kilani's work and then connecting the relevance rationally to the reality of Indonesian Muslim education. There are many beneficial findings from al-Kilani's work that can be used and operated in Indonesian Muslims' education.